Pathophysiological Abnormalities in Functional Dyspepsia Subgroups According to the Rome III Criteria. (January 2017) - Vanheel, H; Carbone, F; Valvekens, L; Simren, M; Tornblom, H; Vanuytsel, T; Van Oudenhove, L; Tack, J
Abstract : Objectives: The Rome III criteria proposed to subdivide functional dyspepsia (FD) into a postprandial distress syndrome (PDS) group, characterized by the presence of postprandial fullness and/or early satiety, and an epigastric pain syndrome (EPS) group, characterized by the presence of epigastric pain and/or epigastric burning. It has been suggested that different pathophysiological mechanisms underlie the symptom presentations in these subgroups that might determine treatment choices. The aim of this study was to investigate the prevalence of gastric sensorimotor dysfunction in the PDS, EPS, and overlap groups and to evaluate potential differential associations with dyspeptic symptom scores. Methods: Consecutive FD patients fulfilling Rome III criteria were recruited and they scored frequency of dyspeptic symptoms (postprandial fullness, early satiety, nausea, bloating, epigastric pain, and epigastric burning) over the past 3 months (0–5; 1=once a month or less, 2=two or three times a month, 3=once a week, 4=several times a week, 5=every day). The cumulative symptom score was calculated by adding up the score of these dyspeptic symptoms. Based on these symptom scores, the patients were subdivided into subgroups according to the Rome III consensus: (i) PDS, characterized by postprandial fullness and/or early satiety at least several times a week, (ii) EPS, characterized by epigastric pain and/or epigastric burning at least once a week, and (iii) overlap, fulfilling the criteria for both PDS and EPS. Gastric sensitivity and gastric accommodation were measured using barostat testing, and solid gastric emptying was determined using the [ 14 C]octanoate breath test. Results: A total of 560 FD patients (165 men, age 41.8±0.7 years) were classified into PDS ( n =131), EPS ( n =50), and overlap ( n =379) groups. The prevalence of gastric hypersensitivity, impaired gastric accommodation, and delayed gastric emptying were 37%, 37%, and 23%, respectively, without any differential distribution in Rome III subgroups ( P =0.16, P =0.27, and P =0.39 respectively). Comparing the physiological parameters for these gastric sensorimotor functions, there was only a significant difference in the gastric half emptying time between subgroups, with the overlap group having a higher t 1/2 ( P <0.05) compared with the EPS group. In the overlap group, gastric hypersensitivity was associated with the severity of PDS symptoms ( P =0.03), EPS symptoms ( P =0.02), and the cumulative symptom score ( P =0.02), whereas delayed gastric emptying was associated with nausea ( P =0.02) and the cumulative symptom score ( P =0.02). Conclusions: Except for gastric emptying in the overlap group, FD subgroups as defined by the Rome III criteria are not differentially associated with putative pathophysiological mechanisms. These observations question the utility of this classification for guiding therapeutic choices in clinical practice.